2019
DOI: 10.11604/pamj.2019.33.256.17061
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic right diaphragmatic rupture with hepatothorax in Ghana: two rare cases

Abstract: A rare case series of traumatic right diaphragmatic rupture with hepatothorax in Ghana is reported. The first case involved a middle-aged man who sustained a penetrating chest injury following an unprovoked attack by a wild bull. The second case was a young woman who sustained a blunt chest injury after being knocked down by a moving vehicle whiles crossing the road. Both presented with ruptured right diaphgramatic rupture and had to undergo repair through thoracotomy after stabilization and the two had been w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In case of complications, surgery is mandatory [23]. Smaller diaphragmatic defects can be primarily closed with a non‐absorbable suture [28, 29] while for larger defects, where the primary suture would develop excessive tension due to the considerable loss of tissue, or also in order to reinforce the suture, meshes should be used [30, 31]. The biologic mesh represents an alternative to the synthetic one due to its lower rate of hernia recurrence, higher resistance to infections and lower risk of displacement [23, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…In case of complications, surgery is mandatory [23]. Smaller diaphragmatic defects can be primarily closed with a non‐absorbable suture [28, 29] while for larger defects, where the primary suture would develop excessive tension due to the considerable loss of tissue, or also in order to reinforce the suture, meshes should be used [30, 31]. The biologic mesh represents an alternative to the synthetic one due to its lower rate of hernia recurrence, higher resistance to infections and lower risk of displacement [23, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…The diaphragmatic defect is usually closed by simple suture, with nonabsorbable sutures for minor defects [ 33 , 34 ]. Any hiatal defect that is larger than 5 cm 2 (the hiatal hernia area (HSA)) has a formal recommendation for reinforcement—if the edges of the defect can be sutured—with either mesh or replacement if aggrandizement is not possible ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five patients had no intrathoracic viscus/organ herniation. Auscultation of bowel sounds in the lower lung zones with dull percussion note may also be suggestive of a possible diaphragmatic rupture with bowel herniation [ 7 , 10 , 13 ]. The preoperative diagnosis of most of our patients was of clinical suspicion, with the most common imaging done being chest X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly implicated associated injuries include shock, respiratory distress and coma [ 3 ]. It has been reported that up to two-thirds of patients with TDR and associated multisystem injuries have had initial diagnosis of the rupture missed, and this accounts for the drastic rise in mortality and morbidity rates [ 13 ]. At least 62% of patients with associated injuries have been documented to have had diagnosis of diaphragmatic rupture missed up until the 4 th day [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation